Effect of CSR, Financial Distress, and Corporate's Growth on Earning Response Coefficient - Adam Martin Immanuel (Universitas Pendidikan Indonesia, 2021)
Abstract. This study aims to obtain empirical evidence on the effect of corporate social responsibility (CSR), financial distress, and corporate growth on earnings response coefficient. This study uses data from manufacturing sector companies listed on the IDX during the period 2017 to 2020. Based on purposive sampling, this study uses a sample of 64 companies with a total of 256 observations. Data were analyzed using multiple regression analysis. The results concluded that corporate social responsibility has a positive effect on the earnings response coefficient, financial distress has a negative effect on the earnings response coefficient, and corporate growth has no impact on the earnings response coefficient. Keywords: corporate growth; corporate social responsibility; earnings response coefficient; financial distress; Indonesia. Abstrak. Penelitian ini bertujuan untuk memperoleh bukti empiris tentang pengaruh corporate social responsibility, financial distress, dan pertumbuhan perusahan pada earnings response coefficient. Populasi penelitian ini adalah perusahaan manufaktur yang tercatat di BEI tahun 2017-2020. Data pada penelitian ini menggunakan data sekunder yang diperoleh dari laporan keuangan dan laporan tahunan perusahaan sampel. Berdasarkan teknik purposive sampling, penelitian ini menggunakan sampel sebanyak 64 perusahaan dengan total observasi sebanyak 256 observasi. Data dianalisis menggunakan analisis regresi berganda. Hasil regresi penelitian ini menunjukkan bahwa corporate social responsibility berpengaruh positif terhadap earnings response coefficient, financial distress berpengaruh negatif terhadap earnings response coefficient, dan pertumbuhan perusahaan tidak berpengaruh terhadap earnings response coefficient. Kata Kunci: corporate social responsibility; earnings response coefficient; financial distress; Indonesia, pertumbuhan perusahaan.